Car pass system its effects on stakeholders - Baylosis, Jerome Kirby H.; de Felipe, Marigold I.; Petinglay, Tessa Joy L.; Siton, Ma. Armilee C.; Teodosio, Rhean B. (2002.)
Executive Summary - The study sought to answer the socio-economic implications of the Car pass System implemented on stakeholders. Specifically, it was intended to find out the process and extent of implementation of the Car Pass System in Iloilo City. It also intended to assess the level of response of the public on the Car Pass System and the effects of the Car Pass System to the stakeholders. Furthermore, this study sought to find out the level of awareness of the public on other traffic experimentations and the means by which problems regarding traffic in the city of Iloilo will be solved. More importantly, this study considered the hypotheses that, the route taken by drivers and commuters, and the ownership of stalls of businessmen in the Iloilo terminal Market has no significant effect on their acceptance of the Car Pass system. The study made use of a descriptive research design wherein data were collected from the respondents from the transport sector, business sector, and the riding public. The research instruments used were three sets of questionnaires. This included separate sets for the peddlers and stall owners, the city and the provincial jeepney drivers, and the city and provincial commuters. To have insights on the implementation of the Car pas System, interview schedules for officers of TMEU and city officials and physical observation were also conducted. These instruments were administered and data obtained were processed for analysis and interpretation using frequency counts, percentages and Chi-square tests for statistical treatment.
[Research Paper] (BA 200 - Business Research) -- [Iloilo City : University of the Philippines in the Visayas - College Management], April 2002.